MOTIVASI DAN IMPLIKASI PENGGUNAAN MEDIA SOSIAL FACEBOOK DI KALANGAN PEMUDA DI DESA NYIUR TEBEL LOMBOK TIMUR - Baiq Miftahul Jannah; Abdullah Muzakar; M. Zainul Asror (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2020)
This study aims to determine the motivation and implications of using Facebook social media among young people in Nyiur Tebel Village. This study uses a qualitative approach with a descriptive type of research. Data collection techniques used are interviews and documentation. While the data analysis technique used is an interactive model of qualitative data analysis through the stages of data reduction, data presentation, and data verification. Based on the study results, it can be reported that the motivation of young people in Nyiur Tebel Village to use both Facebook and other social media has many benefits and negative implications. If not used wisely or handled properly, social media, especially Facebook social media, can make it difficult for young people to socialize with people around them, as happens among young people who prefer to socialize using social media compared to those around them.